Pengaruh Kualitas Pelayanan dan Lokasi terhadap Kepuasan Pengunjung Hotel Grand Palm pada Masa Pandemi di Kota Pematangsiantar - Risma Nuraini Munthe; Elfina OP Damanik; Resna Napitu; Eva Sriwiyanti (J-MAS (Jurnal Manajemen dan Sains), 2022)
This research is motivated by the phenomenon that occurs regarding the level of visitor satisfaction at the Grand Palm Hotel Pematangsiantar which may threaten the integrity in providing visitor services. This of course will affect the number of visitors who stay and use the services of Hotel Grand Palm. The objectives of this study are, (1) To determine the effect of service quality on visitor satisfaction, (2) To determine the effect of location on visitor satisfaction, (3) To determine service quality and location simultaneously influence visitor satisfaction at Grand Palm Hotel Pematangsiantar. The sample that will be taken and researched is 40 visitors of Grand Palm Hotel Pematangsiantar with purposive sampling. Then analyzed the data obtained by using multiple linear regression analysis. This analysis includes: Validity, reliability, multiple regression analysis, hypothesis testing through t and F tests, and analysis of the coefficient of determination (R2). From the results of the analysis obtained regression analysis: Y = 4.521+ 0.089 X1 + 0.293 X2From the results of the t-test, the service quality variable (X1) has a positive and significant effect on visitor satisfaction (Y) with a regression value of 29.23% and a t-count value = 2.923 with a significance level of 0.006. The location variable (X2) has a positive and significant effect on visitor satisfaction (Y) with a regression value of 25.58% and a t-count value = 2.558 with a significant level of 0.015. From the results of the F test, the comparison between F count and F table, where F count is 23,664 greater than F table, which is 3,251, it can be concluded that Ha is accepted or service quality and location have a significant influence on visitor satisfaction. From the results of the coefficient of determination of R2 that has been carried out in this study, the coefficient of determination of R2 is 0.538 or 53.8%. This shows that the percentage of the contribution of the independent variables (service quality and location) to the dependent variable (visitor satisfaction) is 53.8% with the variation of the independent variables used in the model (service quality and location) able to explain 53.8.2% of the dependent variable. (Visitor satisfaction), while the remaining 46.2% is influenced or explained by other variables that are not included in this research model.